Does inward FDI affect outward FDI in tourism in China?. Issue 2 (March 2020) - Song, Changyao; Shi, Shanshan; Chen, Jamie M; Li, Xinjian
Outward foreign direct investment (FDI) from emerging economies has dramatically increased in the tourism industry. Based on the assumption of spillover effects of FDI, this article examines the impact of inward FDI on tourism-based outward FDI. This study applies the negative binomial model to panel data from 2001 to 2015 in China and reveals that FDI inflows and tourism-based FDI inflows are important drivers of China's tourism-based outward FDI. Furthermore, it is found that the level of regional development has a moderating effect on these flows.